Gender Inequity in the Public Health Workforce. Issue 2 (13th March 2022) - Yassine, Brianne Bostian; Rojewski, Jay W.; Ransom, Montrece McNeill
Abstract : Context: Public health is a gendered field. Although a majority of the public health workforce, women encounter an imbalance of power and experience disparate opportunities within the profession. Analysis: This article offers a multidimensional critique of gender inequity within the public health workforce through an examination of the literature. Results: There are three existing disparities between men and women in public health: unequal representation in leadership positions; persistence of wage discrimination; and disparities in scholarly publication and citations. Disparities are often more pronounced among women with intersectional identities (eg, race/ethnicity or other identities). Discussion: Gender inequity is structural, and solutions must address micro-, interactional, and macro-levels. The changing workforce and practitioners' skills in addressing upstream issues provide the opportunity to address this issue.